Keefektivitasan Penggunaan Platform LMS Dalam Pelaksanaan Pembelajaran Jarak Jauh - Restu Pranansha Anugerah; Wahyu Andhyka Kusuma (J-Icon : Jurnal Komputer dan Informatika, 2021)
In the current era, technology has developed very rapidly, where smartphone and laptop users are increasing very rapidly, of course with the help of these tools we can complete various jobs and also to learn. This research was conducted by studying the literature with data collected from several sources related to the topic and by doing this research we can find out how effective the use of LMS is. During the current pandemic, learning was carried out using distance learning methods with many methods, one of which was the Learning Management System (LMS). There are many things that must be considered in the Distance Learning process, including the use of information technology and the given learning model. By utilizing this LMS learning model, the distant learning process can take place effectively.